2008
DOI: 10.1016/j.brainresbull.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects of nicotine and transcranial magnetic stimulation in the olfactory bulbectomy rat model of depression

Abstract: In this study, we compared the depression-like symptoms induced by olfactory bulbectomy (OBX) in the two inbred Wistar and Long Evans rat strains. We also analyzed the self-regulated oral intake of nicotine in these strains and the effect of nicotine on the depression-like symptoms of olfactory bulbectomy. Furthermore, we compared the antidepressant-like effects of nicotine on Wistar rats to those of transcranial magnetic stimulation (TMS), which has emerged as a therapeutic alternative for depression manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 37 publications
2
33
2
Order By: Relevance
“…No therapeutic attempts could be applied between the induction and test phases. One way of overcoming these difficulties in the original FS would be that only the test session alone is used to assess depression-like states induced by other independent methods, including gene modification (Miyamoto et al, 2002) or olfactory bulbectomy (Vieyra-Reyes et al, 2008). However, as a reliable test method for distinguishing antidepressant and anxiolytic drugs, the FS paradigm has been widely used over 30 years.…”
Section: Dual Nature Of Fs Testsmentioning
confidence: 99%
“…No therapeutic attempts could be applied between the induction and test phases. One way of overcoming these difficulties in the original FS would be that only the test session alone is used to assess depression-like states induced by other independent methods, including gene modification (Miyamoto et al, 2002) or olfactory bulbectomy (Vieyra-Reyes et al, 2008). However, as a reliable test method for distinguishing antidepressant and anxiolytic drugs, the FS paradigm has been widely used over 30 years.…”
Section: Dual Nature Of Fs Testsmentioning
confidence: 99%
“…103 Inconsistent with the findings in depressed humans, OBX rats have increased serum BDNF levels. 102 A study by Vieyra-Reyes and her colleagues 104 reviewed the assertion that the cessation of smoking precipitates depressive symptoms. They also showed that olfactory bulbectomy cannot produce depressivelike symptoms in all strains of rats (e.g., no symptoms were developed in the Long Evans rats).…”
Section: Other Alterations In Obx Rats With Possible Novel Therapeutmentioning
confidence: 99%
“…They reported an increase of free consumption of nicotine in OBX animals. 104 To further understand the complexity of the OBX syndrome and its repercussion on neurochemical brain systems in the rat brain, it is important to note the involvement of the opioid system in the development of the OBX syndrome. Subchronic administration of the opioid agonist, SNC80, in OBX rats, reduced hyperemotional responses (struggle, fight, attack, and startle), as well as time spent in an open arm maze.…”
Section: Other Alterations In Obx Rats With Possible Novel Therapeutmentioning
confidence: 99%
“…These effects include antinociception (Aceto et al 1983), sedative and analgesic effect (Mattila et al 1968), alterations in cognition (Levin and Simon 1998) and memory (Zarrindast et al 1996), convulsions and seizure induction (Damaj et al 1999), and antidepression-like effect (Hayase 2011;Mineur and Picciotto 2010;Vieyra-Reyes et al 2008) in experimental animals. Animal studies have demonstrated that both acute and chronic administration of nicotine, without affecting locomotor behavior, exerted antidepressant-like effects in rodent models of depression such as the learned helplessness and forced swimming test (Djurić et al 1999;Tizabi et al 1999).…”
Section: Introductionmentioning
confidence: 97%